Síndrome de burnout y su relación con el desempeño de las funciones de enfermería en el Hospital General Martin Icaza de la ciudad de Babahoyo en los meses de octubre del 2019 a febrero del 2020. - Bricio Garcés, Silvia Kariela (2020)
The presence of burnout syndrome in nursing staff is a silent enemy that threatens health and has a negative impact on the performance of their functions and the quality of care in the service provided to patients. The problem is visualized and analyzed at the Martin Icaza Hospital, Babahoyo, Los Ríos, where the workforce of nurses between nurses and auxiliaries is 109 individuals, of which the sample of 56 nurses is made using non-probabilistic type sampling Intentional by criteria of inclusion and exclusion, descriptive method is applied since the characteristics of the investigation are adjusted to the concrete reality that is explored through observation and survey techniques, where the fundamental instrument was the Maslach Burnout Inventory (MBI) Questionnaire. The results confirm that 62.5% of the nurses suffered greater emotional exhaustion, in general terms in the nursing staff it has a presence of 35.71% in contrast it was possible to identify signs that on the areas of greatest concern being Santa Lucia with 71.43%, in addition to a notable impact on the decrease in the performance of nursing functions. It is concluded that burnout syndrome has a high degree of incidence among nursing staff, in addition to a notable influence on nursing functions, reducing their performance even to an unsatisfactory level.